Interface treatment agent and preparation method thereof
By using interfacial treatment agents prepared by materials such as rigid acrylic composite emulsion and quartz sand, the problem of hollowing of foamed ceramic materials after hot and cold cycles and moisture erosion is solved, and the cell sealing and adhesion durability is improved.
Patent Information
- Application Number
- CN202411989438.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing foamed ceramic materials are prone to hollowing after hot and cold cycles and moisture erosion, resulting in the decorative coating falling off, and the existing interface mortar and ceramic tile interface agent are insufficient.
A paste-like interface treatment agent is prepared for filling and closing bubble cells of foamed ceramics using rigid acrylic composite emulsion as the core gelling material, combined with different grades of quartz sand and preferred heavy calcium, as well as functional additives.
Effective filling and cell closure of foamed ceramics are achieved, the bonding durability is improved, and the stability and aesthetics of the finish layer are ensured.
Smart Images

Figure CN119775926A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an interface treatment agent and a preparation method thereof, which are applied in the field of production of foamed ceramic thermal insulation decorative materials for building exterior walls. Background Art
[0002] Foamed ceramics, also known as foam ceramics, are lightweight ceramic materials with high closed-cell porosity made from mineral raw materials such as clay, quartz, alkali metals or alkaline earth oxides, supplemented by foaming agents, etc., and are made by high-temperature baking and foaming. It has the characteristics of fire retardancy, low thermal conductivity, small deformation coefficient, good strength, and low density, and is widely used in the fields of building fire protection, thermal insulation, and decoration. Due to its porous surface (pore diameter 1-3mm) and dense and smooth porcelain pore walls, it has poor compatibility with other cementitious materials, which can easily cause the finishing layer or bonding layer to hollow out and fall off, limiting its use. Some projects use cement mortar (interface mortar) as the interface filler for foamed ceramics. Although it can better seal the foam pores of foamed ceramics, the durability of the bonding between the interface mortar and the foamed ceramics is insufficient. After hot and cold cycles and moisture erosion, it will easily fall off, causing the finishing paint to fall off. There are also projects that use tile interface agents as foamed ceramic interface agents (such as a tile interface treatment agent and its preparation method CN201210271602.1). Although this tile interface agent increases the bonding strength between the finishing layer and the contact surface of the foamed ceramic, it cannot effectively seal the pores on the surface of the foamed ceramic. It will also produce hollowing after hot and cold cycles and moisture erosion, which will cause the finishing paint to fall off.
[0003] Therefore, it has become an urgent task to provide an interface treatment agent suitable for foamed ceramic filling and reinforcement, with good pore sealing effect and excellent bonding durability, and a preparation method thereof. Summary of the invention
[0004] The invention provides an interface treatment agent and a preparation method thereof, which overcomes the shortcomings of poor pore sealing effect and bonding durability of the existing interface mortar or tile interface agent, adopts a rigid acrylic composite emulsion as a core gelling material, is matched with quartz sand of different preferred gradations as an aggregate, is supplemented with heavy calcium with a preferred mesh size and a preferred functional additive in the system, and has the advantages of being suitable for foamed ceramic filling and reinforcement, having a good pore sealing effect and good bonding durability.
[0005] The technical solution of the present invention is as follows:
[0006] An interface treatment agent is mainly prepared from the following components in the following mass proportions:
[0007]
[0008]
[0009] Among them, the particle size of quartz sand is 40-60 mesh, and the modulus coefficient is 2.3-2.7; the particle size of quartz sand is 60-100 mesh, and the modulus coefficient is 1.7-2.0; the particle size of quartz sand is 20-40 mesh, and the modulus coefficient is 3.3-5.5;
[0010] The rigid acrylic composite emulsion is mainly prepared from the following components in the following mass proportions:
[0011]
[0012] The other monomers are one or any combination of two or more of methacrylic acid monomers, methyl methacrylate monomers or ethyl methacrylate monomers.
[0013] The interface treatment agent of the present application adopts a rigid acrylic composite emulsion as the core cementitious material, with quartz sand of different preferred gradations as aggregate, supplemented with preferred mesh size of heavy calcium and preferred functional additives in the system to form a paste product, which can effectively fill the foam pores of foamed ceramics and form a solid whole with them, and at the same time has good compatibility with other finishing materials or adhesive materials, forming a perfect transition bonding layer, which has the advantages of being suitable for foamed ceramic filling and reinforcement, good pore sealing effect, and good bonding durability. After the rigid acrylic composite emulsion with better preferred bonding effect is formed into a film, it can be effectively bonded to the porcelain interface of foamed ceramics with the assistance of cross-linking agent coupling enhancement. Quartz sand of different gradations can adapt to the pore sizes of different foamed ceramics to achieve saturated filling, so that the surface of the foamed ceramic forms a dense plane.
[0014] The interface treatment agent also includes 0.1-5 parts of quartz sand coarse sand with a particle size of 20-40 meshes and a modulus coefficient of 3.3-5.5.
[0015] The preferred graded quartz sand enables the interface treatment agent to adapt to more pore sizes of different foamed ceramics and achieve saturated filling.
[0016] The interface treatment agent also includes 0.1-5 parts of heavy calcium with a particle size of 750-850 mesh.
[0017] The preferred heavy calcium can fill the voids, increase density and strength, and at the same time improve the workability of the system.
[0018] The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0019] The preferred silane coupling agent builds a "molecular bridge" between the interface of inorganic ceramics and organic coatings, connecting two materials with very different properties together to improve the performance of the composite material and increase the bonding strength.
[0020] The crosslinking agent is 1,6-HDDMA hexanediol dimethacrylate.
[0021] The preferred cross-linking agent participates in the copolymerization polymer of the emulsion, further improving the strength of the emulsion system, thereby better matching the foamed ceramic interface with a high elastic modulus to form a transition interface.
[0022] The emulsifier is sodium alkylbenzene polyether sulfonate, and the initiator is ammonium persulfate.
[0023] Preferred emulsifiers and initiators have better effects.
[0024] The thickeners provided include alkali swelling thickeners and anionic thickeners.
[0025] The method for preparing the interface treatment agent comprises the following steps performed in sequence:
[0026] (I) Preparation of rigid acrylic composite emulsion
[0027] (1) adding acrylic acid monomer, other monomers, an emulsifier accounting for 70-80% of the total weight of the monomers, and water accounting for 80-85% of the total weight of the monomers into a pre-emulsification kettle, and emulsifying for 30-40 minutes to obtain an emulsion without stratification;
[0028] (2) adding the remaining water, the remaining emulsifier, the crosslinking agent, the silane coupling agent and other functional additives except the pH adjuster into the polymerization reaction kettle, and then heating to 78-80° C. and mixing evenly;
[0029] (3) Adding 70-80% of the total mass of the emulsion obtained in step (1) to the polymerization reactor, and then adding 60-70% of the total mass of the initiator, maintaining the mixing reaction at 78-80° C. for 20-30 minutes; then continue to dropwise add the remaining emulsion and the remaining initiator, and complete the dropwise addition within 3-4 hours;
[0030] (4) then raising the temperature of the polymerization reactor to 85-90° C., maintaining the temperature for 1-2 hours, then cooling the temperature to 45-50° C., and adding a pH adjuster to adjust the pH value to 6-7, thereby obtaining the rigid acrylic composite emulsion;
[0031] (II) Preparation of interface treatment agent
[0032] (1) Start the stirring tank, adjust the speed to 500-800 r / min, add 88-92% of the total mass of water and preservatives into the stirring tank, and stir for at least 1 minute;
[0033] (2) maintaining a rotation speed of 500-800 r / min, while stirring, continue to add 50-60% of the total mass of the thickener, stirring for at least 5 minutes, and then add the pH adjuster and stir for at least 3 minutes;
[0034] (3) maintaining the speed of 500-800 r / min, adding rigid acrylic composite emulsion, dispersant, film-forming aid, heavy calcium and defoamer accounting for 70-80% of the total mass of the stirring tank while stirring, washing the inner wall of the stirring tank with water accounting for 2-3% of the total mass of the stirring tank, adjusting the speed to 900-1000 r / min, and stirring for at least 20 minutes;
[0035] (4) Maintaining the speed of 900-1000 r / min, continue to add fine quartz sand, medium quartz sand, coarse quartz sand and the remaining thickener, and stir for at least 15 minutes;
[0036] (5) Maintaining the rotation speed at 900-1000 r / min, continue to add antifreeze and the remaining defoaming agent, wash the inner wall of the stirring tank with the remaining water, adjust the rotation speed to 500-800 r / min, and stir for at least 10 minutes to obtain the interface treatment agent.
[0037] The preparation method of the interface treatment agent of the present application has simple steps and is easy to operate.
[0038] In step (ii) of preparing the interface treatment agent in step (4), coarse quartz sand is also added.
[0039] The addition of quartz sand and coarse sand enables the interface treatment agent to adapt to more pore sizes of different foamed ceramics and achieve saturated filling.
[0040] In step (2) of preparing the interface treatment agent, heavy calcium is also added in step (3).
[0041] The addition of heavy calcium fills the voids, increases density and strength, and also improves the workability of the system.
[0042] Compared with the prior art, the present invention has the following advantages:
[0043] 1) The interface treatment agent of the present application is a paste product prepared by using a rigid acrylic composite emulsion as a core gelling material, quartz sand of different preferred gradations as an aggregate, and a preferred functional additive in the system. It can effectively fill the foamed ceramic pores and form a solid whole with them. At the same time, it has good compatibility with other finishing materials or adhesive materials to form a perfect transition bonding layer. It has the advantages of being suitable for filling and reinforcing foamed ceramics, having good pore sealing effect, and good bonding durability;
[0044] 2) The preparation method of the interface treatment agent has simple steps and is easy to operate.
[0045] Specific implementation party
[0046] The technical solution of the present invention is described in detail below in conjunction with the embodiments of the specification.
[0047] Example 1
[0048] The interface treatment agent described in the present invention is mainly prepared from the following components in the following mass proportions:
[0049]
[0050] Among them, the particle size of quartz sand is 40-60 mesh, and the modulus coefficient is 2.4; the particle size of quartz sand is 60-100 mesh, and the modulus coefficient is 1.8;
[0051] The rigid acrylic composite emulsion is mainly prepared from the following components in the following mass proportions:
[0052]
[0053]
[0054] Among them, the other monomer is a methacrylic acid monomer.
[0055] The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0056] The crosslinking agent is 1,6-HDDMA hexanediol dimethacrylate.
[0057] The emulsifier is sodium alkylbenzene polyether sulfonate.
[0058] The initiator is ammonium persulfate.
[0059] The method for preparing the interface treatment agent comprises the following steps performed in sequence:
[0060] (I) Preparation of rigid acrylic composite emulsion
[0061] (1) adding acrylic acid monomer, other monomers, an emulsifier accounting for 75% of the total weight of the monomers, and water accounting for 82% of the total weight of the monomers into a pre-emulsification kettle, and emulsifying for 35 minutes to obtain an emulsion without stratification;
[0062] (2) adding the remaining water, the remaining emulsifier, the crosslinking agent, the silane coupling agent and other functional additives except the pH adjuster into the polymerization reaction kettle, and then heating to 79° C. and mixing evenly;
[0063] (3) Adding 70-80% of the total mass of the emulsion obtained in step (1) to the polymerization reactor, and then adding 65% of the total mass of the initiator, maintaining the mixing reaction at 79° C. for 25 minutes; then continue to dropwise add the remaining emulsion and the remaining initiator, and complete the dropwise addition within 3.5 hours;
[0064] (4) then raising the temperature of the polymerization reactor to 88° C., maintaining the temperature for 1.5 hours, then cooling the temperature to 47° C., and adding a pH adjuster to adjust the pH value to 6.5, thereby obtaining the rigid acrylic composite emulsion;
[0065] (II) Preparation of interface treatment agent
[0066] (1) Start the stirring tank, adjust the speed to 600 r / min, add 90% of the total mass of water and preservatives into the stirring tank, and stir for at least 1 min;
[0067] (2) Maintaining the rotation speed at 600 r / min, continue to add the alkali swelling thickener while stirring for 5 minutes, then add the pH adjuster and stir for at least 3 minutes;
[0068] (3) Maintaining the speed at 600 r / min, the rigid acrylic composite emulsion, dispersant, film-forming aid, heavy calcium and defoamer accounting for 75% of the total mass of the stirring tank are continuously added while stirring, and the inner wall of the stirring tank is washed with water accounting for 3% of the total mass of the stirring tank, and the speed is adjusted to 950 r / min and stirred for 20 min;
[0069] (4) Maintaining the rotation speed at 950 r / min, continue to add fine quartz sand, medium quartz sand, coarse quartz sand and anionic thickener, and stir for 15 minutes;
[0070] (5) Maintaining the rotation speed at 950 r / min, continue to add antifreeze and the remaining defoaming agent, wash the inner wall of the stirring tank with the remaining water, adjust the rotation speed to 600 r / min, and stir for 10 minutes to obtain the interface treatment agent.
[0071] Example 2
[0072] The interface treatment agent described in the present invention is mainly prepared from the following components in the following mass proportions:
[0073]
[0074] Among them, the particle size of quartz sand is 40-60 mesh, and the modulus coefficient is 2.3; the particle size of quartz sand is 60-100 mesh, and the modulus coefficient is 2.0;
[0075] The rigid acrylic composite emulsion is mainly prepared from the following components in the following mass proportions:
[0076]
[0077] The other monomers are any combination of methacrylic acid monomers and methyl methacrylate monomers.
[0078] The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0079] The crosslinking agent is 1,6-HDDMA hexanediol dimethacrylate.
[0080] The emulsifier is sodium alkylbenzene polyether sulfonate.
[0081] The initiator is ammonium persulfate.
[0082] The method for preparing the interface treatment agent comprises the following steps performed in sequence:
[0083] (I) Preparation of rigid acrylic composite emulsion
[0084] (1) adding acrylic acid monomer, other monomers, an emulsifier accounting for 70% of the total weight of the monomers, and water accounting for 85% of the total weight of the monomers into a pre-emulsification kettle, and emulsifying for 30 minutes to obtain an emulsion without stratification;
[0085] (2) adding the remaining water, the remaining emulsifier, the crosslinking agent, the silane coupling agent and other functional additives except the pH adjuster into the polymerization reaction kettle, and then heating to 80° C. and mixing evenly;
[0086] (3) Adding 70% of the total mass of the emulsion obtained in step (1) to the polymerization reactor, and then adding 70% of the total mass of the initiator, and maintaining the mixing reaction at 78° C. for 30 minutes; then continue to dropwise add the remaining emulsion and the remaining initiator, and complete the dropwise addition within 3 hours;
[0087] (4) then raising the temperature of the polymerization reactor to 90° C., maintaining the temperature for 1 hour, then lowering the temperature to 50° C., and adding a pH adjuster to adjust the pH value to 6, thereby obtaining the rigid acrylic composite emulsion;
[0088] (II) Preparation of interface treatment agent
[0089] (1) Start the stirring tank, adjust the speed to 800 r / min, add 88% of the total mass of water and preservatives into the stirring tank, and stir for 1.5 min;
[0090] (2) Maintaining the rotation speed at 800 r / min, continue to add the alkali swelling thickener while stirring for 5.5 min, and then add the pH adjuster and stir for 3.5 min;
[0091] (3) Maintaining the speed at 800 r / min, the rigid acrylic composite emulsion, dispersant, film-forming aid, heavy calcium and defoamer accounting for 70% of the total mass of the stirring tank are continuously added while stirring, and the inner wall of the stirring tank is washed with water accounting for 3% of the total mass of the stirring tank, and the speed is adjusted to 1000 r / min and stirred for 25 min;
[0092] (4) Maintaining the rotation speed at 1000 r / min, continue to add quartz sand fine sand, quartz sand medium sand, quartz sand coarse sand and anionic thickener, and stir for 20 minutes;
[0093] (5) Maintaining the rotation speed at 1000 r / min, continue to add antifreeze and the remaining defoaming agent, wash the inner wall of the stirring tank with the remaining water, adjust the rotation speed to 800 r / min, and stir for 15 minutes to obtain the interface treatment agent.
[0094] Example 3
[0095] The interface treatment agent described in the present invention is mainly prepared from the following components in the following mass proportions:
[0096]
[0097]
[0098] Among them, the particle size of quartz sand is 40-60 mesh, and the modulus coefficient is 2.7; the particle size of quartz sand is 60-100 mesh, and the modulus coefficient is 1.7;
[0099] The rigid acrylic composite emulsion is mainly prepared from the following components in the following mass proportions:
[0100]
[0101] The other monomers are any combination of methacrylic acid monomers, methyl methacrylate monomers and ethyl methacrylate monomers.
[0102] The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0103] The crosslinking agent is 1,6-HDDMA hexanediol dimethacrylate.
[0104] The emulsifier is sodium alkylbenzene polyether sulfonate.
[0105] The initiator is ammonium persulfate.
[0106] The method for preparing the interface treatment agent comprises the following steps performed in sequence:
[0107] (I) Preparation of rigid acrylic composite emulsion
[0108] (1) adding acrylic acid monomer, other monomers, an emulsifier accounting for 80% of the total weight of the monomers, and water accounting for 80% of the total weight of the monomers into a pre-emulsification kettle, and emulsifying for 40 minutes to obtain an emulsion without stratification;
[0109] (2) adding the remaining water, the remaining emulsifier, the crosslinking agent, the silane coupling agent and other functional additives except the pH adjuster into the polymerization reaction kettle, and then heating to 78° C. and mixing evenly;
[0110] (3) Adding 80% of the total mass of the emulsion obtained in step (1) to the polymerization reactor, and then adding 60% of the total mass of the initiator, and maintaining the mixing reaction at 80° C. for 20 minutes; then continue to dropwise add the remaining emulsion and the remaining initiator, and complete the dropwise addition within 4 hours;
[0111] (4) then raising the temperature of the polymerization reactor to 85° C., maintaining the temperature for 2 hours, then cooling the temperature to 45° C., and adding a pH adjuster to adjust the pH value to 7, thereby obtaining the rigid acrylic composite emulsion;
[0112] (II) Preparation of interface treatment agent
[0113] (1) Start the stirring tank, adjust the speed to 500 r / min, add 92% of the total mass of water and preservatives into the stirring tank, and stir for 2 minutes;
[0114] (2) Maintaining the rotation speed at 500 r / min, continue to add the alkali swelling thickener while stirring for 6 minutes, and then add the pH adjuster and stir for 4 minutes;
[0115] (3) Maintaining the speed at 500 r / min, the rigid acrylic composite emulsion, dispersant, film-forming aid, heavy calcium and defoamer accounting for 80% of the total mass of the stirring tank are continuously added while stirring, and the inner wall of the stirring tank is washed with water accounting for 2% of the total mass of the stirring tank, and the speed is adjusted to 900 r / min and stirred for 30 min;
[0116] (4) Maintaining the rotation speed at 900 r / min, continue to add quartz sand fine sand, quartz sand medium sand, quartz sand coarse sand and anionic thickener, and stir for 25 minutes;
[0117] (5) Maintaining the rotation speed at 900 r / min, continue to add antifreeze and the remaining defoaming agent, wash the inner wall of the stirring tank with the remaining water, adjust the rotation speed to 500 r / min, and stir for 15 minutes to obtain the interface treatment agent.
[0118] Raw material information involved in each embodiment:
[0119] Silane coupling agent: γ-glycidyloxypropyltrimethoxysilane, Tesco Chemical (Hubei) Co., Ltd. Tesco Chemical (Hubei) Co., Ltd. KH-560.
[0120] Experimental data:
[0121] 1. Performance Testing
[0122] Each embodiment was tested according to the standard Q / SKSP193-2024 "Foamed Ceramic Companion", and the test results are shown in Table 1 below:
[0123] Table 1 Performance test results of each embodiment
[0124]
[0125]
[0126] It can be seen that the interface treatment agents of various embodiments have excellent water resistance and bonding strength.
[0127] 2. Comparative Experiment
[0128] Comparative sample 1: Interface mortar: Corbett Concrete, Corbett (Guangxi) New Materials Co., Ltd.
[0129] Comparative sample 2: Tile interface treatment agent (CN201210271602.1)
[0130] Detection method:
[0131] The "Jinyitao" brand I-grade foamed ceramics are selected as the substrate, and its physical properties are shown in Table 2 below:
[0132] Table 2 Physical properties of Class I foamed ceramics of "Jinyitao" brand
[0133]
[0134] Each comparative sample and the sample of Example 1 were coated at a coating rate of 1 kg / m 2 The foamed ceramic surface was painted and naturally dried in the laboratory for 7 days before being sprayed with stone-like paint. A physical property comparison test was conducted three days later. The results are shown in Table 3 below:
[0135] Table 3 Physical properties test results of each sample
[0136]
[0137]
[0138] It can be seen that the pore sealing effect, bonding durability and other properties of the special filling and reinforcing interface agent for foamed ceramics of the present application are better than those of the currently used interface mortar, tile interface treatment agent and the like.
Claims
1. An interface treatment agent, characterized in that: It is mainly prepared by the following components in the following mass proportions: Among them, the particle size of quartz sand is 40-60 mesh, and the modulus coefficient is 2.3-2.7; the particle size of quartz sand is 60-100 mesh, and the modulus coefficient is 1.7-2.0; the particle size of quartz sand is 20-40 mesh, and the modulus coefficient is 3.3-5.5; The rigid acrylic composite emulsion is mainly prepared from the following components in the following mass proportions: The other monomers are one or any combination of two or more of methacrylic acid monomers, methyl methacrylate monomers or ethyl methacrylate monomers.
2. The interface treatment agent according to claim 1, characterized in that: The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
3. The interface treatment agent according to claim 1, characterized in that: The crosslinking agent is 1,6-HDDMA hexanediol dimethacrylate.
4. The interface treatment agent according to claim 1, characterized in that: The emulsifier is sodium alkylbenzene polyether sulfonate, and the initiator is ammonium persulfate.
5. The interface treatment agent according to claim 1, characterized in that: The thickener includes an alkali swelling thickener and an anionic thickener.
6. The method for preparing the interface treatment agent according to any one of claims 1 to 5, characterized in that: The steps are as follows: (I) Preparation of rigid acrylic composite emulsion (1) adding acrylic acid monomer, other monomers, an emulsifier accounting for 70-80% of the total weight of the monomers, and water accounting for 80-85% of the total weight of the monomers into a pre-emulsification kettle, and emulsifying for 30-40 minutes to obtain an emulsion without stratification; (2) adding the remaining water, the remaining emulsifier, the crosslinking agent, the silane coupling agent and other functional additives except the pH adjuster into the polymerization reactor, and then heating to 78-80° C. and mixing evenly; (3) Adding 70-80% of the total mass of the emulsion obtained in step (1) to the polymerization reactor, and then adding 60-70% of the total mass of the initiator, maintaining the mixing reaction at 78-80° C. for 20-30 minutes; then continue to dropwise add the remaining emulsion and the remaining initiator, and complete the dropwise addition within 3-4 hours; (4) then raising the temperature of the polymerization reactor to 85-90° C., maintaining the temperature for 1-2 hours, then cooling the temperature to 45-50° C., and adding a pH adjuster to adjust the pH value to 6-7, thereby obtaining the rigid acrylic composite emulsion; (II) Preparation of interface treatment agent (1) Start the stirring tank, adjust the speed to 500-800 r / min, add 88-92% of the total mass of water and preservatives into the stirring tank, and stir for at least 1 minute; (2) maintaining a rotation speed of 500-800 r / min, while stirring, continue to add 50-60% of the total mass of the thickener, stirring for at least 5 minutes, and then add the pH adjuster and stir for at least 3 minutes; (3) maintaining the speed of 500-800 r / min, adding rigid acrylic composite emulsion, dispersant, film-forming aid, heavy calcium and defoamer accounting for 70-80% of the total mass of the stirring tank while stirring, washing the inner wall of the stirring tank with water accounting for 2-3% of the total mass of the stirring tank, adjusting the speed to 900-1000 r / min, and stirring for at least 20 minutes; (4) Maintaining the speed of 900-1000 r / min, continue to add fine quartz sand, medium quartz sand, coarse quartz sand and the remaining thickener, and stir for at least 15 minutes; (5) Maintaining the rotation speed at 900-1000 r / min, continue to add antifreeze and the remaining defoaming agent, wash the inner wall of the stirring tank with the remaining water, adjust the rotation speed to 500-800 r / min, and stir for at least 10 minutes to obtain the interface treatment agent.
Citation Information
Patent Citations
Tile interface treating agent and preparation method thereof
CN102795827A